2020
DOI: 10.1099/jgv.0.001471
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant subtype A and B human respiratory syncytial virus clinical isolates co-infect the respiratory tract of cotton rats

Abstract: Human respiratory syncytial virus (HRSV) is an important respiratory pathogen causing a spectrum of illness, from common cold-like symptoms, to bronchiolitis and pneumonia requiring hospitalization in infants, the immunocompromised and the elderly. HRSV exists as two antigenic subtypes, A and B, which typically cycle biannually in separate seasons. There are many unresolved questions in HRSV biology regarding the interactions and interplay of the two subtypes. Therefore, we generated a reverse genetics system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In another study, rHRSV A11 expressing EGFP and rHRSV B05 expressing dTom were used in cotton rats and cotton rat cell lines. Occasional double-infected cells were observed, both in vitro and in vivo (27). Our data confirm these observations, with as added value that we use primary human epithelial cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In another study, rHRSV A11 expressing EGFP and rHRSV B05 expressing dTom were used in cotton rats and cotton rat cell lines. Occasional double-infected cells were observed, both in vitro and in vivo (27). Our data confirm these observations, with as added value that we use primary human epithelial cells.…”
Section: Discussionsupporting
confidence: 87%
“…rHRSV A2 [rHRSV A2 EGFP(5)] was commercially obtained from ViraTree (product no. R125), and previously rescued rHRSV A11 [rHRSV A11 EGFP(5), passage 5]; rHRSV B05 rHRSV B05 EGFP(5), passage 6; and rHRSV B05 dTom(5), passage 7 have been described before (the 5 between brackets refers to the position of the additional transcriptional unit in the genome) (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Once the FeMV US5 sequence was available from these amplicons, FeMV US5 -specific primers ( SI Appendix , Table S2 , U122 and US5 designations) were designed for cDNA synthesis, PCR, and sequencing. Rapid amplification of cDNA ends was used to generate amplicons containing leader and trailer sequences as previously described ( 79 ); these were sequenced to determine the authentic genomic termini of FeMV US5 . Sequences were aligned in DNAstar SeqMan Pro software (Lasergene), and contigs were generated corresponding to the consensus sequence.…”
Section: Methodsmentioning
confidence: 99%
“…The high-copy phagemid vector pBluescript has been previously reported to be a suitable vector for construction of fulllength cDNA clones for rhabdoviruses and paramyxoviruses (53)(54)(55) and also RSV strains belonging to the GA1 and BA genotypes (41,42). In contrast, we have found that use of pBluescript KS(+) as a vector backbone for full-length cDNA clones consistently results in full or partial deletions of the G gene of both RSV-A and -B strains.…”
Section: Discussionmentioning
confidence: 76%
“…Although these systems have proved invaluable in advancing our understanding of RSV molecular biology and pathogenesis, it is important to more rigorously examine well-documented RSV subtype and strain differences using panels of recombinant viruses based on currently circulating strains for which the consensus sequence of the parental virus of the patient has been determined. This approach has recently been used to construct reverse genetics systems for RSV-A and -B based on strains classified within the GA2 and BA genotypes, respectively, in which the pBluescript KS(+) phagemid vector was used as the vector backbone (41,42). The use of a high-copy vector backbone in these studies contrasts with earlier reverse genetics systems, and the extent to which this strategy can be generalized and applied to other RSV strains without concomitant instability of cloned viral sequences is unknown.…”
mentioning
confidence: 99%